Strengthening Strategies for Students' Spiritual and Social Attitudes in Facing the Fourth Industrial Revolution - Erina Felinda Kusuma; Indhira Asih Vivi Yandari; Reksa Adya Pribadi (International Journal of Education, Information Technology, and Others, 2023)
The purpose of this study is to describe the strategies for strengthening spiritual and social attitudes during the era of the 4.0 industrial revolution at SDIT Bina Bangsa. This research is a descriptive qualitative study. The subjects of this research are the School Principal, Islamic Education Teacher, 5th Grade Class Teacher, and 5th Grade Students. Data collection techniques used in this study include observation, interviews, and documentation. The researcher used triangulation of sources and methods to ensure data validity. The results of the study are as follows: (1) strategies for strengthening spiritual attitudes through learning; (2) strategies for strengthening spiritual attitudes through school activities; (3) strategies for strengthening spiritual attitudes through extracurricular activities; (4) strategies for strengthening social attitudes through learning; (5) strengthening social attitudes through school activities; and (6) strengthening social attitudes through extracurricular activities. In conclusion, the research findings suggest that spiritual and social attitudes can be enhanced through learning, relevant school activities, and extracurricular activities.